Hereditary transthyretin amyloidosis: predictors of conduction disease. (25th November 2020) - Dias De Frias, A.F; Rodrigues, P; Trepa, M; Fontes-Oliveira, M; Costa, R; Campinas, A; Hipolito-Reis, A; Torres, S
Abstract: Introduction: Pacemakers are frequently needed due to a high prevalence of conduction disease in mutated ATTR amyloidosis (mATTR). We aimed to identify the variables associated with the need of pacemaker implantation in this population. Methods: We retrospectively studied 255 patients with suspicion of heart involvement of mATTR observed at our cardiology clinic during the last year. Clinical and outcome data were retrieved by chart review. We have defined the need for pacemaker implantation as: 1) the formal guidelines indications or 2) Ventricular pacing >10% in patients who had prophylactic pacemaker implantation prior to liver transplantation (LT). This way, we have defined 3 different groups: group 1: patients with no evidence of conduction disease; group 2: patients with conduction disease, but no formal indication for pacemaker implantation; and group 3: patients with formal indication for pacemaker implantation or ventricular pacing >10% in patients who had prophylactic pacemaker implantation prior to hepatic transplantation. Results: We included 255 patients (50±14 years, 53% male, 52.5% treated with tafamidis and 27% had prior LT, and 10% with atrial fibrillation), 43.3% with no evidence of conduction disease, 32.3% with conduction disease, but no formal indication for pacemaker implantation and 24.4% with formal indication for pacemaker implantation. Patients with formal indication for pacemaker implantation were older, with longer duration of neurologic manifestations, with higher concentration of both Troponin T and NT-proBNP and with higher number of organs affected. In multivariate analysis, longer duration of neurologic manifestations (OR 1.090 – 95% IC: 1.036–1.145, p-value 0.001), Left ventricular (LV) maximal wall thickness (OR 1.230 – 95% CI: 1.070–1.414, p-value 0.004), neurologic staging (OR 3.420 – 95% CI: 1.443–8.104, p-value 0.005) and higher number of organs affected (OR 1.719 – 95% CI: 1.218–2.424, p-value 0.002) all showed to be independent predictors of the need for pacemaker implantation, in contrast to LV ejection fraction and serum concentration of Troponin T and NT-proBNP. We've also found a statistical significant association between conduction disease and ophthalmic manifestations. Conclusions: Our findings suggest that the need for pacemaker implantation in patients with mATTR is closer linked to the duration, severity and affected number of organs than to cardiac biomarkers or echocardiographic findings. Funding Acknowledgement: Type of funding source: None